To Message or Browse? Exploring the Impact of Phone Use Patterns on Male Adolescents’ Consumption of Palatable Snacks - Teo, Ethan; Goh, Daniel; Vijayakumar, Kamalakannan M.; Liu, Jean C. J. (Frontiers in Psychology, 2018)
Surveys of mobile phone usage suggest that adolescents habitually use their phones while eating. In this study, we explored whether the manner in which one uses a mobile phone – to engage in a social or non-social activity – can affect appetite regulation. Participants were fifty male adolescents randomly assigned to engage in one of the following phone-based activities: (1) sending and receiving messages (social activity), or (2) reading a neutral article (non-social activity). When given the opportunity to snack, participants in the messaging group consumed more snacks that those who read the article. Our findings correspond to a large literature emphasising social influences on food intake, and suggest that phone use patterns may predispose an individual to overeating.